Personality Dispositions and their Relationship with Team Cohesion - Yogalakshmi, J. A.; Supriya, M. V.; Kirthana, (Prabandhan: Indian Journal of Management, 2016)
Much research has been done to explore the relationship between personality dispositions and various concepts like career success, job satisfaction, organization's commitment, and so forth. The current study attempted to explore the impact of four personality dispositions on team cohesion, which is considered to be an important ingredient for the success of any team (team effectiveness). Correlation and multiple regression analysis were implemented to draw the results which predicted that emotional stability and conscientiousness are the most significant predictors of team cohesion, which confirmed the results of previous studies on team cohesion ; whereas, self-esteem and extraversion did not significantly contribute to team cohesion.